Short-term effects on soil properties and wheat production from secondary paper sludge application on two Mediterranean agricultural soils - Nunes, J. Rato (2013)
This study was conducted under greenhouse conditions to evaluate the potential use of SPS as a fertilizer, amendment and/or liming agent for wheat (Triticum aestivum L.). Two representative Mediterranean agricultural soils, a Cambic Arenosol (cmAR) and a Cromic Cambisol (crCM) were used. Treatments included four sludge rates ranging from 0 to 40 g kg 1 (equivalent of 0, 38, 88 and 120 Mg ha 1). A significant increment in soil pH, organic carbon, N total, available P and exchangeable K were observed in both soils. Sludge application significantly increased N and decreased Zn, Mn and Cu concentrations in wheat. Wheat grain yields were reduced by 33% and 37% when 120 Mg SPS ha 1 was applied to cmAR and crCM soils, respectively, due apparently to unavailability of Mg. However, straw yields, with much lower Mg requirements, increased significantly with SPS rates. Secondary pulp mill sludge seems to be a potential source of organic matter, N, P, K and a potential soil amendment liming agent for acid soils, when appropriate supplemental fertilizer was provided. For grain crops grown in these soils, addition of Mg is required for proper nutrient balance.